Nascent proteomes of ischemic-injured and ischemic-tolerant neuronal cells. (18th February 2011) - Zhou, An; Simon, Roger P.; David, Larry
In a recent study on ischemic rodent brains, we quantitatively characterised and compared brain proteomes under ischemic-preconditioned or injured or tolerant conditions. We discovered an enriched presence of repressive transcriptional regulator proteins with essential roles as epigenetic regulators in ischemic-tolerant brains (Stapels et al., 2010). We further showed their robust, dynamic and differential changes under different ischemic conditions in brains and in cultured neuronal cells. In the present work, using neuronal cell cultures, we aimed to characterise the nascent proteome, the proteome that presents early when the cells receive an ischemic insult. These would be the proteomic changes of newly synthesised proteins. Identification of effectors of this phase of response to ischemia bears the best promise of identifying therapeutic targets for treating acute stroke when patients present to hospital. We compared these nascent proteomes across different ischemic conditions using bioinformatic tools.